Cassava based foods: how safe are they? - Bokanga, M.; Otoo, E. (International Society for Horticultural Science, 1994)
Cassava production in Africa has increased by 12.5% between 1988 and 1990 with Nigeria becoming the largest cassava producer in the world. Almost all of the African cassava production is destined for human consumption. The consumption of cassava is sometimes associated with toxicity due to its cyanogenic potential (CNP). This paper presents the results of a preliminary survey of the CNP of cassava foods consumed in Kumasi, Ghana. The traditional processing of cassava in Africa and its potential for detoxification are reviewed. It is concluded that a large proportion of the CNP of cassava foods is in the form of intact cyanogenic glucosides. In animal trials, cyanogenic glucosides have shown little toxicity. Permissible levels of cyanide in foods and beverages established by various regulatory agencies range from zero to 250 ppm. It is recommended that detailed toxicological studies be conducted on the cyanogenic glucosides of cassava and that a maximum acceptable level for the CNP of cassava and cassava foods be proposed.